Pengaruh Struktur Modal, Likuiditas, Aktivitas, Ukuran Perusahaan terhadap Kesulitan Keuangan - Wihandaru Sotya Pamungkas; Alien Akmalia; Silvia Dian Rizki Saputri (Universitas Jember, 2024)
This study aims to find empirical evidence of the effect of capital structure, liquidity, activity, and company size on financial distress (KK). The sample used is companies listed on the Indonesia Stock Exchange (IDX) engaged in the consumer goods sector in 2016-2020. The sampling technique uses purposive sampling with financial statement criteria in rupiah and explicitly lists operating profits. The number of samples analyzed was 305 units. The analysis tool uses binary logistic regression. The results obtained are that the capital structure (SM) has a significant positive effect on KK, liquidity (LIK) has a significant negative effect on KK, activity (AKT) has a significant negative effect on KK, and company size (UP) has a significant negative effect on KK. Keywords: Financial Distress, Capital Structure, Liquidity, Activity, Firm Size